The Effect of the Gadgets Use on Motivation and Learning Outcomes of Class VI Students in Al-Quran Hadith Lessons at MI Al-Muwazanah Kediri - Agus Miftakus Surur; Fitri Khoirun Nikmah; Dewi Rizqi Ilyana Nuzula; Lu’lu’im Mansyuroh; Choirum Minatun Hasanah (EDUCARE: Journal of Primary Education, 2022)
Today's school-age children are also affected by technological developments that target other groups. The natural growth process of school-age children can be disrupted due to the use of gadgets. For this reason, it is necessary to have a motivation to learn so they can still carry out learning activities well. This study attempts to explain the relationship between student learning motivation and the intensity of using gadgets and student learning outcomes to explain the effect of using gadgets on student motivation and learning outcomes. This study uses a quantitative approach involving data in the form of numbers. The instruments used are questionnaires and documentation. Through a questionnaire, data will be obtained in the form of numbers which are then analyzed using an application. At the same time, documentation is used to support processes related to research. This study obtained the results that there was a significant relationship between the use of gadgets and students' learning motivation. This motivation is evidenced by a questionnaire or questionnaire submitted to students, namely as respondents, after being tested for correlation. With the results shown from the results of this study, it is hoped that the use of gadgets is more directed and guided so that the motivation given can increase student enthusiasm in participating in learning. Anak usia sekolah masa kini ikut terkena imbas perkembangan teknologi, yang juga menyasar kalangan lain. Proses tumbuh kembang alami anak usia sekolah dapat terganggu akibat penggunaan gadget. Untuk itu, perlu adanya motivasi belajar sehingga mereka tetap dapat melakukan aktivitas pembelajaran dengan baik. Penelitian ini berusaha menjelaskan keterkaitan motivasi belajar siswa dengan intensitas penggunaan gadget dan hasil belajar siswa, menjelaskan pengaruh pengaruh penggunaan gadget terhadap motivasi dan hasil belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif yang melibatkan data berupa angka-angka. Instrumen yang digunakan berupa angket dan dokumentasi. Melalui angket, akan diperoleh data berupa angka-angka yang kemudian dianalisis dengan menggunakan aplikasi, sedangkan untuk dokumentasi digunakan untuk mendukung proses yang terkait dengan penelitian. Penelitian ini memperoleh hasil bahwa terdapat hubungan yang signifikan antara penggunaan gadget dengan motivasi belajar siswa. Hal ini dibuktikan dengan angket atau kuesioner yang diajukan kepada siswa yakni sebagai responden setelah di uji berkorelasi. Dengan hasil yang ditunjukkan dari hasil penelitian ini, diharapkan penggunaan gadget lebih diarahkan dan dibimbing, sehingga motivasi yang diberikan dapat meningkatkan antusias siswa dalam mengikuti pembelajaran.